2006
DOI: 10.3164/jcbn.38.51
|View full text |Cite
|
Sign up to set email alerts
|

Rat Cytokine-Induced Neutrophil Chemoattractant-1 (CINC-1) in Inflammation

Abstract: Summary Rat cytokine-induced neutrophil chemoattractant-1 (CINC-1) belongs to the CXCchemokine family and is a counterpart of human growth-related oncogene (GRO) in the interleukin-8 (IL-8) family. In rats, CINC-1 plays a key role in neutrophil-mediated inflammatory diseases by attracting neutrophils to the site of inflammation. Although IL-8 is a well-known chemokine in humans, it remains difficult to investigate human inflammatory diseases in detail. Therefore CINC-1 is expected to be an excellent tool for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…For neutrophils, it is the result of excessive defense reactions of the human body against H. pylori intrusion, and for H. pylori, it is a convenient tool for invading the human gastric mucosa. Although the role of H. pyloriinduced oxidative stress in gastric epithelial cells is not clear, it might be involved in signal transduction in epithelial cells [20,21], or in gastric carcinogenesis. Further study is required to elucidate the role of H. pylori-induced oxidative stress in gastric epithelial cells and gastric carcinogenesis.…”
Section: Ros/rns Production In H Pylori-infected Gastric Mucosamentioning
confidence: 99%
“…For neutrophils, it is the result of excessive defense reactions of the human body against H. pylori intrusion, and for H. pylori, it is a convenient tool for invading the human gastric mucosa. Although the role of H. pyloriinduced oxidative stress in gastric epithelial cells is not clear, it might be involved in signal transduction in epithelial cells [20,21], or in gastric carcinogenesis. Further study is required to elucidate the role of H. pylori-induced oxidative stress in gastric epithelial cells and gastric carcinogenesis.…”
Section: Ros/rns Production In H Pylori-infected Gastric Mucosamentioning
confidence: 99%
“…It is speculated that neutrophils are activated by and react to microcirculation injury by rolling, adhesion, extravasation, and infiltration into a site via adhesion molecules induced by inflammatory cytokines and that mediators released from activated neutrophils induce organ injury [15,16] . Thus, inflammatory cytokines, in particular IL-8, are greatly involved [17,18] , and the roles of IL-8 in the pathogenesis of ischemia-reperfusion injuries have been investigated by using anti-IL-8 antibodies [19] .…”
Section: Controlmentioning
confidence: 99%
“…Thrombin is known to have inflammatory functions via G protein-coupled receptors, including proteaseactivated receptor-1 (PAR1) (3,15). It has been reported that PAR1 induces rat cytokine-induced neutrophil chemoattractant-1 (CINC-1), a CXC chemokine of the interleukin-8 family (7,8), release (30) and that thrombin stimulates proinflammatory production in vivo (31) and in vitro (4,20,28). However, the role of the thrombin/PAR1 pathway in intestinal I-R has not yet been investigated.…”
mentioning
confidence: 99%